Ibrutinib-Induced Vasculitis in a Patient with Metastatic Colon Cancer Treated in Combination with Cetuximab - Jeffrey Chi; Jennifer Park; Muhammad Wasif Saif (Case Reports in Oncological Medicine)
Combination therapy with ibrutinib and cetuximab is being studied in a phase 1b/2 trial in patients with advanced gastrointestinal and genitourinary malignancies. Rash is a common cutaneous adverse effect for both medications. Ibrutinib is a Bruton’s tyrosine kinase (BTK) inhibitor approved for the treatment of several hematologic malignancies. The rash can be asymptomatic, nonpalpable, mild skin eruption, or palpable purpuric rash. A rarer panniculitis form has also been reported. Cetuximab, an epidermal growth factor (EGFR) inhibitor, approved for treatment in head and neck and advanced gastrointestinal malignancies is also known to cause acneiform rash in majority of patients. The rash is due to inhibition of EGFR in the basal keratinocytes and hair follicles. In the case of ibrutinib, the off-target effects on EGFR, c-kit, and platelet-derived growth factor receptor (PDGFR) are thought to be responsible for the cutaneous eruption of various forms of rash. The combination therapy with the BTK inhibitor and a direct EGFR inhibitor may potentiate the rash inducing effects of the drugs. Here, we describe a case of vasculitis in a patient with metastatic colon cancer who received both ibrutinib and cetuximab on a phase Ib/II clinical trial.